ANALISIS TAKSIRAN KERUGIAN PIUTANG PADA KOPERASI SIMPAN PINJAM BERAU KALTIM DI TANJUNG REDEB - AMINS, DAWAMI BUCHORI (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2017)
The purpose of this research is to know the estimated loss of accounts receivable at Berau Kaltim Cooperative in TanjungRedeb. The analytical tools used to test the hypothesis are age analysis of receivables and estimated loss of accounts receivable. From the analysis it can be seen that the estimated value of loss of accounts receivable according to Berau Kaltim Cooperative is Rp. 4.454.100, - while the estimated value of loss of accounts receivable according to the calculation using the method of age analysis of receivables is Rp. 2.841.010, - or there is a difference of Rp. 1.613.090, -. Therefore the estimated value of loss of accounts receivable by Berau Kaltim Cooperative Rp. 4,454,100, - greater than the estimated value of loss of accounts receivable according to the method of age analysis of receivables Rp. 2.841.010, -then it can be said that the estimated amount of losses on receivables at Berau Kaltim Cooperative has not been set optimally, then the hypothesis proposed in this research is accepted.